2017
DOI: 10.1002/adfm.201701245
|View full text |Cite
|
Sign up to set email alerts
|

Glycine N‐Methylation in NGR‐Tagged Nanocarriers Prevents Isoaspartate Formation and Integrin Binding without Impairing CD13 Recognition and Tumor Homing

Abstract: NGR (asparagine-glycine-arginine) is a tumor vasculature-homing peptide motif widely used for the functionalization of drugs, nanomaterials, and imaging compounds for cancer treatment and diagnosis. Unfortunately, this motif has a strong propensity to undergo rapid deamidation. This reaction, which converts NGR into isoDGR, is associated with receptor switching from CD13 to integrins, with potentially important manufacturing and pharmacological and toxicological implications. It is found that glycine N-methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…It seems, therefore, that glycine N ‐methylation does not impair the tumor‐homing properties of the NGR peptide and increases its tumor selectivity, possibly by preventing isoDGR formation. These studies have also shown that this peptide can be used for the development of drug nanocarriers that are more stable and selective than those obtained with conventional NGR peptides, including peptide‐tagged liposomal doxorubicin and gold nanoparticles . Thus, this novel NGR derivative could represent a valid alternative to conventional NGR peptides for liposome functionalization.…”
Section: How To Improve Ngr‐liposome Stability and Selectivitymentioning
confidence: 94%
See 3 more Smart Citations
“…It seems, therefore, that glycine N ‐methylation does not impair the tumor‐homing properties of the NGR peptide and increases its tumor selectivity, possibly by preventing isoDGR formation. These studies have also shown that this peptide can be used for the development of drug nanocarriers that are more stable and selective than those obtained with conventional NGR peptides, including peptide‐tagged liposomal doxorubicin and gold nanoparticles . Thus, this novel NGR derivative could represent a valid alternative to conventional NGR peptides for liposome functionalization.…”
Section: How To Improve Ngr‐liposome Stability and Selectivitymentioning
confidence: 94%
“…Remarkably, this change prevents the deamidation reaction without impairing CD13 binding (see Figure ). Studies performed in mice‐bearing solid tumors have demonstrated that this NGR‐derivative is more selective for tumor tissues than the corresponding isoDGR and NGR peptides . In particular, although these studies showed similar accumulation of radiolabeled methylated NGR and the corresponding NGR and isoDGR peptides (cyclicCGNGRG and CisoDGRG) in tumors (fourfold, compared to blood and other tissues), in the case of the NGR and isoDGR peptides a certain degree of accumulation was observed also in other organs, such as stomach, spleen, liver, intestine, and femur.…”
Section: How To Improve Ngr‐liposome Stability and Selectivitymentioning
confidence: 94%
See 2 more Smart Citations
“…We have previously shown that peptides containing isoAsp‐Gly‐Arg (isoDGR), a motif that recognizes the αvβ3 integrin overexpressed in tumor vessels and on different tumor cell types, can be exploited as ligands for targeted delivery of various drugs and nanoparticles to tumors 16b,17. In particular, we have identified a head‐to‐tail‐cyclized hexapeptide, CGisoDGRG (called Iso1), which recognizes αvβ3 with high selectivity and affinity, binds tumor vessels, and works as an efficient ligand for delivering fluorescent nanoparticles or radioactive compounds to tumors . The Iso1 peptide, after chemical conjugation to human serum albumin, has been exploited for tagging gold nanoparticles loaded with tumor necrosis factor‐alpha (TNF), a cytokine endowed with antitumor activity .…”
Section: Introductionmentioning
confidence: 99%